IMPROVING THE STUDENTS’ SOCIAL CARE CHARACTER IN THE SUB-TOPIC OF NATIONALISM SPIRIT GROWTH AND DEVELOPMENT THROUGH THE METHOD OF VALUE CLARIFICATION TECHNIQUE (VCT) IN SOCIAL SCIENCE LEARNING - Merian, Fertilia Dwi (Universitas Pendidikan Indonesia, 2019)
This study was initiated by the researcher’s finding at VIII-B class SMP Negeri 3 Lembang where the students social care character has not been noticeable yet; the students are less capable to respect other people and to cooperate. The students still utter the harsh words to their friends. This study employed the classroomaction research by Kemmis dan Taggart in three cycles. This study used Value Clarification Technique (VCT) method that encourage the students to comprehend and apply the in-effect rules and values in the society and develop the social care character. This study found that their caring character improves more obvious in every cycle. This study was stopped and finished when the students’ bad character and habits shows some significant changes into a better way. The findings show that the method of Value Clarification Technique in Social Science learning improves the students’ social care character at VIII-B class in SMP Negeri 3 Lembang.